The Influence of Price, Service Quality, and Store Atmosphere on Purchase Decisions on Awesam Malang Distro Consumers - Koko Endro Prasetiyo; Rahmad Wijaya; Yulist Rima Fiandari (Jamanika (Jurnal Manajemen Bisnis dan Kewirausahaan), 2023)
The purpose of this study is to test and analyze the effect of price on purchasing decisions at Awesam, to test and analyze the effect of service quality on purchasing decisions at Awesam, to test and analyze the effect of store atmosphere on purchasing decisions at Awesam, to find out and analyze price, quality variables. services and store atmosphere that have a dominant influence on purchasing decisions on Awesam. The type of survey used is a quantitative survey with a total sample of 100 respondents. The population in this study are consumers who have made purchases at the Awesam distro in Malang City. The data analysis technique uses multiple regression analysis with the t-test. From the results of the research and discussion conducted, it can be concluded that price has a significant effect on purchasing decisions. service quality has a significant effect on purchasing decisions, store atmosphere has a significant effect on purchasing decisions and price has a dominant effect on purchasing decisions.